Impact of examined lymph node number on accurate nodal staging and long-term survival of resected Siewert type II-III adenocarcinoma of the esophagogastric junction: A large population-based study - Ding, Baicheng; Yong, Jiahui; Zhang, Lixiang; Luo, Panquan; Song, Endong; Rankine, Abigail N.; Wei, Zhijian; Wang, Xingyu; Xu, Aman (Frontiers in Oncology, 2022)
Abstract Background. We aimed to investigate the association between the number of examined lymph nodes (ELNs) and accurate nodal staging and long-term survival in Siewert type II-III Adenocarcinoma of the Esophagogastric Junction (AEG) by using large population-based databases and determined the optimal ELN number threshold. Methods. Data on Stage I-III Siewert type II-III AEG patients from 2010 to 2014 respectively from the United States (US) SEER database and a Chinese large medical center institutional registry were analyzed for correlation between the ELN number and stage migration (node negative-to-positive) and overall survival (OS) by using multivariable-adjusted logistic and Cox regression models, respectively. The series of odds ratios (ORs), and hazard ratios (HRs) were fitted with a LOWESS smoother, and the structural breakpoints were determined by Chow test. The selected optimal cut point was then validated with the 2015 to 2016 SEER database. Results. Both the US cohort(n=1387) and China cohort(n=981) showed significantly increases from node-negative to node-positive disease (ORtheUS1.032,95%CI 1.017–1.046;ORChina1.034,95%CI 1.002–1.065) and enhancements in overall survival (HRtheUS0.970,95%CI 0.961-0.979;HRChina0.960,95%CI 0.940-0.980) with the increasing ELN number after controlling for confounders. Associations for both stage migration and overall survival were still significant in most subgroups’ stratification. Cut point analysis showed a threshold ELN number of 18, which was validated both in the cohorts where it originated and in an independent SEER data cohort(n=379). Conclusions. More ELNs are associated with accurate nodal staging(negative-to-positive) as well as higher overall survival in resected Siewert types II-III AEG, We recommend 18 ELNs as the optimal cut point for the quality assessment of postoperative lymph node examination or prognostic stratification in clinical practice.